High standards of teaching in practice. (2nd June 2022) - Oldman, Crystal
Abstract : Since the withdrawal of NMC practice teacher standards, the qualification has ceased to be offered by many higher education institutions. New standards are due to be published by the QNI in the coming months, says Crystal Oldman